Analysis on the acceptance of paddy growers towards price stabilization programme at Sungai Kerang, Teluk Intan, Perak / Nur Shafira Ismail - Ismail, Nur Shafira (Faculty of Plantation and Agrotechnology, 2019)
Paddy crop in our country was low in the production which is produce rice only for self-sufficiency level for Malaysians and as the food security Malaysia dependent on the imported rice from neighbour country was about 30%. Malaysia rice industry was still low in the productivity to produce rice even there were many supports from government to help them. The aim of this study was analyse the acceptance of paddy growers (as the dependent variable) based on the three (3) factors of price stabilization programme (independent variables) by government which were ceiling price, floor price and subsidy. The objective of this survey were to evaluate the factors that affected acceptance of paddy growers towards price stabilization programme and to evaluate the most dominant factor that influence acceptance of paddy growers. This study was focused on the paddy growers at the specific area at Kampung Sungai Kerang, Teluk Intan, Perak. The method of this study was done by distributing questionnaires to 103 respondents who stay in the area of study. The result has been analysed by using Statistical Package for Social Science (SPSS) for factor analysis and stepwise regression. The most dominant factor was floor price which influenced acceptance of paddy growers towards price stabilization programme. The study may give benefits to several area of researcher where it can help farmers itself, government and next researcher to make this study as the references. For that reason, government should continuously provide price stabilization programme in order to facilitate paddy growers protect their income.